Assessment of S-76 rotor hover performance in ground effect using an unstructured mixed mesh method - Hwang, Je Young; Kwon, Oh Joon (Aerospace science and technology, 2019)
In the present study, the aerodynamic performance of an S-76 rotor in hover was numerically investigated by using an unstructured mixed mesh flow solver. The study was made for the rotor for both OGE (out-of-ground-effect) and IGE (in-ground-effect) conditions, and the results are compared against each other. In the present mixed mesh methodology, body-fitted prismatic/tetrahedral mesh was adopted in the near-body flow domain to treat complex geometries easily and to capture the viscous layer on the solid surface more accurately, while in the off-body region away from the blades Cartesian mesh was used. To better resolve the flow characteristics and to prevent excessive numerical dissipation, a high-order accurate weighted essentially non-oscillatory (WENO) scheme was employed in the off-body flow region. An overset mesh topology was adopted to handle blade rotation and to exchange the flow variables between the two different mesh regions. The calculations were made for three different blade configurations, having swept-tapered, rectangular, and swept-tapered-anhedral tip shapes, and the results are compared with experimental rotor performance data in terms of thrust, torque and figure of merit. The predictions were obtained for a collective pitch angle sweep from 5 to 10 degrees at a tip Mach number of 0.60 for both with and without ground effects. The detailed flow characteristics, such as vorticity contours and tip-vortex trajectory, were also investigated.